Effect of annexin-A1 peptide treatment during lung inflammation induced by lipopolysaccharide - da Cunha, Esther Emanuella [UNESP]; Oliani, Sonia Maria [UNESP]; Damazo, Amilcar Sabino (Academic Press Ltd Elsevier B.V. Ltd, 2012)
Lung endotoxemia is characterized by neutrophil accumulation, increased vascular permeability and parenchymal injury. This can also affect the endogenous pathways that operate in the host to keep inflammation under control. Here, we demonstrate differential expression of annexin-A1 (AnxA1) protein in mice after the local or intraperitoneal administration of lipopolysaccharide (LPS; 1 mg/kg) in mice and the regulation of the endotoxemic inflammation after the pre-treatment with the AnxA1 peptidomimetic Ac2-26. The intranasal administration of LPS induced the leukocyte migration and cytokine release to the alveolar space, whereas the peritoneal administration of LPS generated a deregulated cellular and cytokine response, with a marked degree of leukocyte adhesion in the microcirculation. The peptide Ac2-26 pre-treatment inhibited the leukocyte migration and the pro-inflammatory cytokine release. Also, it induced the expression of endogenous AnxA1 and the antiinflammatory cytokine IL-10. In conclusion, our data obtained from endotoxemia induced by local or intraperitoneal LPS administration suggested that the molecular mechanisms induced by AnxAl peptidomimetic Ac2-26 lead to the regulation of leukocyte activation/migration and cytokine production induced by LPS. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Annexin A1; Lung; Lipopolysaccharide; Macrophage; Neutrophil; Interleukin-10